Corporate Sustainable Development. Revisiting the Relationship between Corporate Social Responsibility Dimensions. (30th October 2017) - Ait Sidhoum, Amer; Serra, Teresa
Abstract: With rising stakeholder concerns over sustainable development, corporate social responsibility (CSR) has become key for the business community, moving the business model beyond financial performance to a new voluntary paradigm based on natural resource conservation, social welfare, stakeholder engagement and economic performance. This article aims to answer whether profitable business is compatible with balanced sustainability by investigating the relationship between the economic, social, environmental and governance performance for a sample of global firms. A canonical vine (C‐vine) copula is used for this purpose. Results show the existence of a fairly strong positive relationship between economic, social and environmental performance. The corporate governance dimension is shown to have a weak relationship with the rest of the CSR dimensions. Important policy implications are derived from these results. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment